Detailed in utero ultrasound description of 30 cases of congenital cytomegalovirus infection. (18th March 2014) - Picone, O.; Teissier, N.; Cordier, A. G.; Vauloup‐Fellous, C.; Adle‐Biassette, H.; Martinovic, J.; Senat, M. V.; Ayoubi, J. M.; Benachi, A.
ABSTRACT Objectives The aim of this research was to describe precisely prenatal ultrasound (US) features in congenital cytomegalovirus (CMV) infection. Methods We retrospectively evaluated the US descriptions of cases of congenital CMV infection between 2004 and 2013. Results In 69 congenital CMV infections, related US abnormalities were reported in 30 cases (43.5%). There were both extracerebral and cerebral abnormalities in 16 cases, purely abnormal brain features in ten, and purely extracerebral features in two. About 19/30 cases presented extracerebral features of 11 different sorts of abnormalities, mainly hyperechogenic bowel (ten cases) and intrauterine growth retardation (nine cases). About 24/30 cases presented cerebral features of 13 different sorts, mainly brain calcifications (12 cases) and occipital horn cavity (11 cases). The main US findings in our series are not specific to CMV infection. However, a frequent finding attracted our attention: the anechogenic cavity located on the extremity of the occipital horn, a region which contains numerous proliferating and differentiating germinal cells. Conclusions By improving knowledge of US findings linked to CMV infection, US sensitivity may be improved. Understanding why CMV leads to lesions of the occipital horn may help clarify the pathophysiology of congenital infection. © 2014 John Wiley & Sons, Ltd.